(untitled) (Педагогіка вищої та середньої школи, 2009)
In the article examined possibility of using the technique of improvisation as developing force, as the meaning of development creative potential of students. as possibilities of transformation previous experience in the new style. Accent belongs on the improvisation technique, which allows to set with itself and outward things to new. realized and more active relations.